Performance of Guinea grass (Panicum maximum Jacq cv. Likoni) forage area according to the population of wire grass (Sporobolus indicus L.) - Paduilla, C?sar; Sardi?as, Yurangel; Febles, Gustavo; Curbelo, F. (Cuban Journal of Agricultural Science, 2012)
The influence of wire grass (Sporobolus indicus. L) (0, 2, 4 and 6 plants/m2) on yield, cost and quality of Guinea grass (Panicum maximum Jacq cv. Likoni) biomass was studied in a calcic ferralic soil, through a completely random design and ten repetitions. The wire grass height did not vary with the increase of its population and the area of the soil covered was increased (P < 0.001). There was an inverse ratio (r = -0.88) (P < 0.001) between Guinea grass yield and wire grass population. The forage cost increased from 25.21 to 78.63 pesos, for 0 and 6 plants of wire grass/m2, respectively. The chemical composition of the soil did not vary with the treatments. The highest wire grass population produced lower (P < 0.05) content of organic matter digestibility (OMD) and Ca (P < 0.01). There was no effect on the chemical composition of Guinea grass. In the wire grass, only CP and P were lower (P < 0.01) with the population increase. It is concluded that the increase of wire grass population diminished the Guinea grass yield, elevated the cost of biomass production and altered some indicators of forage quality. Further studies on the possible effects of wire grass population on biomass quality of improved pastures are recommended. Key words: Panicum maximum, Sporobolus indicus, weeds population, yield, cost